Evaluación del Factor de Necrosis Tumoral (TNF-alfa) en pacientes peruanos con procesos periodontales - Taboada Vega, Manuel Enrique (2007)
The tumor necrosis factor (TNF) is an important mediator of the inflammatory reactions; it seems to play a central roll in the pathogenesis of several chronic inflammatory diseases including the periodontitis. It has been demonstrated that different rates exist from TNF alpha in vitro and in vivo between the individuals, so it can be associated with the presence of certain genetic polymorphism. The purpose of this investigation is to study the degree of polymorphism of the gene TNF-alpha (-308G/A) in samples of adult Peruvian patients and analyze the relationship with periodontal processes. For the study 81 blood samples with anticoagulant EDTA of people between 25 and 52 years were collected (47,5 average ± 7,4). 11 of them were people who had severe periodontal processes (average 35,2 ± 2,3). There was a greater frequency of genotype GG (G alele for the gene TNF-alpha-308) of the 82,86% in healthy people and 63,63% in people with periodontal processes. While the genotype AA (A alele for the gene TNF-alpha-308) that is related to a greater increase of TNF-alpha synthesis, was of 18,8%, this value was not very significant according to the chi-square test. The results are according to some works that find direct association between the polymorphism of the gene TNF-alpha with the periodontal processes, but not with others that do associate it. Since the periodontitis is considered a multifactorial disease the polymorphism of TNF-alpha -308 (G/A) in Peruvian patients is discussed.